HUMANITY IN THE META-GALAXY: ANTHROPOLOGY’S SHIFTING PERSPECTIVES - Родриге, Барри (History, Archeology and Ethnography of the Caucasus, 2019)
We humans engage in a constant process of enlarging our understanding of the world around us. As our ancestors spread throughout Africa and beyond, they developed innovative strategies for survival – from tools and clothing to languages and customs. When dispersed human groups came into contact with each other, they shared ideas and genes. Self-awareness is a result of such interactions. This merging led to intercultural thinking of humanity as a global community, which in turn led to the birth of what we call anthropology. It was a method of self-actualization – by better comprehending our place in the world, we adapted ourselves and our surroundings. We are again at the threshold of a new self-awareness, a product of the consolidation of scholarship and global contacts to form what has been called cosmic evolution, big history, and universal studies. This expanded worldview is a product of taking a sense of a unified humanity to the next level – to the recognition that we are but one of many symbiotic life forms on Earth and but one entity within a much larger cosmos. The multiverse is commonly seen as a larger entity of which our universe is a component. Although there are many uses of the term, some quite divergent, a big history perspective by astronomer Tom Gehrels is the one that is in mind for this essay. The concept of a multiverse also serves as a metaphor for the variety of ways of seeing and interpreting existence.
Keywords: Anthropology; Civilization; Universal Humanity; Multiverse; Big History.